2013
DOI: 10.21273/hortsci.48.12.1556
|View full text |Cite
|
Sign up to set email alerts
|

White Clover (Trifolium repens) Establishment within Dormant Bermudagrass Turf: Cultural Considerations, Establishment Timing, Seeding Rate, and Cool-season Companion Grass Species

Abstract: White clover (Trifolium repens L.) inclusion is a proposed means of increasing the sustainability of certain low-maintenance turfgrass scenarios through increased pollinator habitat and as a result of the legume’s ability to biologically fix atmospheric nitrogen (N). Proper white clover establishment is key to maximizing stand uniformity and N contribution to associated grasses. However, there are few guidelines for white clover establishment within warm-season turfgrasses. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Additionally, reduced turfgrass canopy can also increase production of legume stolons (Ballar e et al, 1995). McCurdy et al (2013) reported similar results in bermudagrass, where SC produced much higher WC germination than nonscalping treatments. While CA, on average, did not lower turf quality below an acceptable level, it also did not provide as favorable of an environment for WC germination and establishment as SC and VM.…”
Section: Resultssupporting
confidence: 56%
“…Additionally, reduced turfgrass canopy can also increase production of legume stolons (Ballar e et al, 1995). McCurdy et al (2013) reported similar results in bermudagrass, where SC produced much higher WC germination than nonscalping treatments. While CA, on average, did not lower turf quality below an acceptable level, it also did not provide as favorable of an environment for WC germination and establishment as SC and VM.…”
Section: Resultssupporting
confidence: 56%
“…The number of plants establishing in plots can be difficult to determine for species with spreading vegetation, so aboveground vegetative units appropriate for the species were quantified on the premise it would correlate to the number of individuals establishing in a plot. This method has been most commonly applied for T. repens in the form of trifoliate leaves (McCurdy et al, 2013;Sparks et al, 2015), and was adopted here for additional species. Vegetative units were considered any structure that arose from the ground and could be reasonably counted over the entire plot.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have found effects of turfgrass species on forb establishment. A recent study involving white clover co-seeded with companion grasses into dormant bermudagrass found clover produced more trifoliate leaves in tall fescue compared with the faster growing varieties such as annual ryegrass (McCurdy et al, 2013). A similar study used three species of turfgrass co-seeded with birdsfoot trefoil (Lotus corniculatus L.), and found that kentucky bluegrass and red fescue typically had greater yields of birdsfoot trefoil than perennial ryegrass (Laskey and Wakefield, 1978).…”
Section: Discussionmentioning
confidence: 98%
“…An ideal turfgrass species would maintain groundcover, but also allow for establishment and bloom of its forb companions. Some effort has been made into developing seeding strategies for white clover into established lawns to benefit pollinators and soil nitrogen (McCurdy et al, 2013;Sparks et al, 2015). White clover is an established agronomic crop that is widely associated with pasture agriculture, and is well adapted to the grazing systems under which it evolved (Leffel and Gibson, 1973).…”
mentioning
confidence: 99%